Sexually Transmitted Infections Detected by Multiplex Real Time PCR in Asymptomatic Women and Association with Cervical Intraepithelial Neoplasia - Lima, Luiza de Miranda; Hoelzle, Carolina René; Simões, Renata Toscano; Lima, Maria Inês de Miranda; Fradico, Jordana Rodrigues Barbosa; Mateo, Elvis Cristian Cueva; Zauli, Danielle Alves Gomes; Melo, Victor Hugo (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To determine the frequency of sexually transmitted infections (STIs) in asymptomatic women and the association of STIs with cervical intraepithelial neoplasia (CIN).Methods A cross-sectional study was performed, enrolling women examined in a general gynecology clinic and in a colposcopy referral center from October 2014 to October 2015. The colposcopy group consisted of 71 women, and the general gynecology group consisted of 55 women. Cervical samples were collected for cervical cytology and a multiplex real-time polymerase chain reaction (PCR) was developed to detect human papillomavirus (HPV) and the STIs caused by the following microorganisms: Chlamydia trachomatis, Mycoplasma hominis, Mycoplasma genitalium, Ureaplasma urealyticum, and Neisseria gonorrhoeae. A multivariate analysis was performed by logistic regression, considering the significance level of 0.05.Results The general frequency of STIs was: 46.8% (HPV); 27.8% (C. trachomatis); 28.6% (M. genitalium); 0.8% (M. hominis); 4.8% (U. urealyticum); and 4.8% (N. gonorrhoeae). The significant risk factors for CIN were: HPV infection (odds ratio [OR] = 2.53; p = 0.024); C. trachomatis (OR = 3.04; p = 0.009); M. genitalium (OR = 2.37; p = 0.04); and HPV and C. trachomatis coinfection (OR = 3.11; p = 0.023). After the multivariate analysis, a significant association was found between HPV and CIN (OR = 2.48; 95% confidence interval [95%CI]: 1.04–5.92; p = 0.04); and between C. trachomatis and CIN (OR = 2.69; 95%CI: 1.11–6.53; p = 0.028).Conclusion The frequency of STIs was high in asymptomatic patients. Infections by HPV and C. trachomatis were independently associated with the presence of CIN. The high frequency of STIs in asymptomatic women suggests the need for routine screening of these infections.
Keywords: papillomavirus infections; chlamydia; sexually transmitted diseases; polymerase chain reaction; cervical intraepithelial neoplasia